Rediscovery of the Canary Islands endemic Aphaenogaster hesperia Santschi, 1911 (Hymenoptera, Formicidae, Myrmicinae) - Pérez-Delgado, Antonio J.; Lugo, David; Santos-Perdomo, Irene; Jiménez-García, Eduardo; Suárez, Daniel (Zootaxa, 2023)
The Canary Islands endemic species Aphaenogaster hesperia Santschi, 1911 was described based solely on two workers captured in a north-western coastal area of Tenerife (Canary Islands) in 1902 and 1903. The species has not been recorded in the last 100 years and only information on its type locality is known. This species, belonging to the crocea group, has been recently rediscovered in a new site within a pine forest at 950 m a.s.l. The new area is a very different habitat, revealing a lack of ecological knowledge of the species, which may have caused the species to have remained unnoticed for more than 100 years. Novel distributional and morphological data are provided.